2015
DOI: 10.1109/jstars.2014.2330691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Surface Irregularities on the Diurnal Variation of Soil Broadband Blue-Sky Albedo

Abstract: This paper quantitatively explores, in terms of roughness indices, the effect of soil surface irregularities on the diurnal variation of the broadband blue-sky albedo of a large range of soil properties. Field studies were carried out on cultivated and uncultivated soil surfaces in Poland and Israel that vary in roughness and brightness. It was found that these irregularities, formed by different agricultural equipment and modified by rain or sprinkler irrigation, can be quantified by two roughness indices. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…In our case, the gaps in the α b F data sets resulted from the need to reject those data measured when cirrus clouds obscured the sun. The soil blue-sky albedo measurements carried out in Poland and Israel [23], also confirmed by the data generated using a hemispherical-directional model [24], indicate that the blue-sky α b of extremely rough soil surfaces rises slightly from θ s at local noon to about 75 • -80 • of the θ s , while the α b of smooth soils clearly increases throughout the θ s range. Assuming that such behavior of the soil albedo with respect to the θ s is correct, the data representing a decrease in the α b F with increasing θ s were considered incorrect.…”
Section: Resultssupporting
confidence: 63%
“…In our case, the gaps in the α b F data sets resulted from the need to reject those data measured when cirrus clouds obscured the sun. The soil blue-sky albedo measurements carried out in Poland and Israel [23], also confirmed by the data generated using a hemispherical-directional model [24], indicate that the blue-sky α b of extremely rough soil surfaces rises slightly from θ s at local noon to about 75 • -80 • of the θ s , while the α b of smooth soils clearly increases throughout the θ s range. Assuming that such behavior of the soil albedo with respect to the θ s is correct, the data representing a decrease in the α b F with increasing θ s were considered incorrect.…”
Section: Resultssupporting
confidence: 63%
“…We distinguish between surface roughness that refers to microrelief of soil surfaces due to variations and arrangement of soil aggregates (Lehrsch et al 1987;Guzha 2004) from the general relief of a surface that represents topographical structures that are many times larger than soil aggregates. Studies of heat and mass transfer from terrestrial surfaces have shown that land relief and surface roughness may affect the surface reflectively (albedo) hence the amount of shortwave radiation absorbed at the surface (Bowers and Hanks 1965;Potter et al 1987;Raupach and Finnigan 1997;Matthias et al 2000;Cierniewski et al 2014). Surface roughness and relief have also been shown to act as momentum sinks for the atmospheric flows (Raupach 1992) affecting the aerodynamic boundary layer and turbulent interactions adjacent to the surface (Perry et al 1969;Taylor and Gent 1974;Finnigan 1988;Wieringa 1993;Raupach and Finnigan 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the diffuse light ratio, the smaller the impact of θ s on the albedo. Cierniewski et al [16] analysed the diurnal albedo variations of soils to find that soil roughness affected not only the overall level of those variations, but also that the intensity of its increase from θ s at the local noon, to about 75 • -80 • . Surfaces of rough and deep ploughed soils showed almost no rise in albedo values at θ s lower than 75 • , while the same soil, but smoothed, exhibited a gradual albedo increase at these angles.…”
Section: Introductionmentioning
confidence: 99%